Edukasi Pemanfaatan Bahan Alam sebagai Asi Booster pada Ibu Hamil dan Menyusui - Novitarini; Muhammad Eka Putra Ramandha; Baiq Yulia Hasni Pratiwi; Lalu Busyairi Muhsin; Mia Ariasti; Sri Winarni Sofya (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Low levels of exclusive breastfeeding will increase the risk of stunting and susceptibility to disease in the future. One of the reasons for this low supply is that breast milk production is not smooth, so it is necessary to facilitate the production of breast milk from natural ingredients. This service aims to educate about using natural ingredients to enable breast milk for pregnant and breastfeeding mothers. This service method has 4 stages: namely approach, preparation, delivery of material, and discussion. The results of the service showed that the village community understood the natural ingredients that could be used to facilitate breast milk, namely katuk leaves, turi, spinach and banana blossoms. Apart from that, in the service, proper processing is demonstrated so that the content is not lost or reduced. The conclusion of this service is that the community of Preparation Reban Madani village will utilize natural ingredients with proper processing to facilitate breast milk so that they can carry out exclusive breastfeeding. The implication of community service is that village knows how to process local plants to facilitate breast milk.